Challenges of International Students from Pre-Departure to Post-Study: A Literature Review - Khanal, Jeevan; Gaulee, Uttam (Journal of International Students, 2019)
Studying in overseas universities or colleges presents international students with exciting opportunities; however, with these opportunities come challenges that they need to overcome. The purpose of this review is to summarize the challenges of international students. Drawing on the existing literature since the year 2000, this article addresses several challenges confronting international students within some top sending countries and receiving countries. The challenges are categorized into pre-departure, post-departure, and post-study to create a model of the issues of international students. The findings revealed a plethora of challenges including some common ones such as obtaining accurate information, admission procedure, and preparing documents for VISA while preparing for study abroad. Similarly, international students have to deal with language, financial challenges, and cultural adjustment when they are in host countries. Uncertain future and paperwork are the major challenges after graduation.